KARAKTERISTIK KEPEMIMPINAN GEN Z PADA PERGURUAN TINGGI : PERSPEKTIF PSIKOANALISIS SIGMUN FREUD - Azmi, Diinu Tsabitul; Susilo, Mohamad Joko (Khazanah: Jurnal Mahasiswa, 2024)
This study investigates the leadership characteristics of Generation Z (Gen Z), particularly within higher education settings, from an educational psychology perspective. The importance of this research stems from Gen Z's distinct leadership style, which often coexists with emotional volatility and mental development challenges. The primary objective is to identify Gen Z's leadership characteristics and unveil the psychological factors in the educational domain that contribute to their leadership effectiveness. To this end, the research applies Sigmund Freud's psychoanalytic framework. The methodology employs a descriptive qualitative approach supported by a comprehensive literature review. Data were gathered from scholarly publications and reliable sources, using keywords such as "Gen Z leadership," "educational psychology," and "Freudian psychoanalysis." Data analysis was conducted using descriptive qualitative methods, integrating literature findings with Freud's psychoanalytic theory. The research findings are expected to present a comprehensive overview of Gen Z's leadership dynamics, including their strengths and inherent limitations. The implications of this study are vital for formulating effective support strategies to optimize Gen Z's leadership potential in the future.